Let's talk about drug abuse - Kreiner, Anna. (New York : The Rosen Publ., 1996)
A simple introduction to different drugs and how they affect the body and to the problem of drug abuse.
Includes index.
Keywords: Drug abuse; Drugs; Drugs of abuse; Drug abuse